A Challenging Treatment Decision for a Rare Association: Case Report of Familial Turcot Syndrome With Fistulizing Crohn's Disease - Montserrat Corbera-Hincapie; Genie L. Beasley (Frontiers Media S.A., 2018)
Turcot syndrome and fistulizing Crohn's disease (CD) are two disease entities that are not usually associated with one another, particularly given the rarity of the former. This is a case of a pediatric patient with fistulizing CD treated with biologic therapy, who was later found to have Turcot syndrome. Management of this rare combination of diseases can present several challenges, as surgical options may be limited and chronic immunosuppression to treat CD may lead to accelerated progression of malignancy in Turcot syndrome. This unique case highlights the importance of weighing the risks and benefits involved in treating two disease entities that impact one another.